A volumetric three-dimensional evaluation of invasiveness of an endoscopic and microscopic approach for transmeatal visualisation of the middle ear. Issue 5 (22nd May 2021) - Baazil, A H A; Dobbe, J G G; van Spronsen, E; Ebbens, F A; Dikkers, F G; Streekstra, G J; de Wolf, M J F
Abstract: Objective: This study aimed to compare the necessary scutum defect for transmeatal visualisation of middle-ear landmarks between an endoscopic and microscopic approach. Method: Human cadaveric heads were used. In group 1, middle-ear landmarks were visualised by endoscope (group 1 endoscopic approach) and subsequently by microscope (group 1 microscopic approach following endoscopy). In group 2, landmarks were visualised solely microscopically (group 2 microscopic approach). The amount of resected bone was evaluated via computed tomography scans. Results: In the group 1 endoscopic approach, a median of 6.84 mm 3 bone was resected. No statistically significant difference (Mann–Whitney U test, p = 0.163, U = 49.000) was found between the group 1 microscopic approach following endoscopy (median 17.84 mm 3 ) and the group 2 microscopic approach (median 20.08 mm 3 ), so these were combined. The difference between the group 1 endoscopic approach and the group 1 microscopic approach following endoscopy plus group 2 microscopic approach (median 18.16 mm 3 ) was statistically significant (Mann–Whitney U test, p < 0.001, U = 18.000). Conclusion: This study showed that endoscopic transmeatal visualisation of middle-ear landmarks preserves more of the bony scutum than a microscopic transmeatal approach.